Spatial Segregation and Gentrification in Metropolitan Urban Space: Dynamics of Socio-Economic Inequality, Marginalization of Urban Poor Communities, and Territory Restructuring Based on Urban Ecology Theory (International Journal of Economics Management and Social Science, 2026)
Metropolitan cities in the Global South are increasingly confronted with a paradox of urban development: while economic growth accelerates and skylines transform dramatically, vast segments of the urban population are pushed further to the margins — geographically, economically, and socially. This article examines the dynamics of spatial segregation and gentrification in Indonesian metropolitan cities, situating them within the theoretical framework of urban ecology and political economy. Drawing on qualitative and quantitative evidence from secondary data, policy documents, and existing empirical studies, this research analyzes how processes of urban restructuring systematically disadvantage the urban poor through displacement, loss of livelihood access, and erosion of social capital. The study argues that spatial segregation in Indonesian metropolitan contexts is not merely an outcome of market forces, but rather a product of deliberate policy decisions, land capital accumulation by elites, and the historical legacies of colonial spatial ordering. Using urban ecology theory — particularly the concepts of natural area formation, invasion-succession, and zone differentiation — alongside critical perspectives from urban political economy, this article demonstrates how gentrification operates as a mechanism for accumulation by dispossession. Findings indicate that communities in peri-urban and inner-city zones face compounding vulnerabilities when urban renewal programs are implemented without participatory safeguards. The article concludes by calling for a reorientation of urban planning toward spatial justice, emphasizing inclusive governance, community land trusts, and participatory spatial planning as countermeasures to market-driven urban restructuring. Keywords: spatial segregation, gentrification, urban ecology, urban poor, metropolitan, socio-economic inequality, dispossession